2018
DOI: 10.1002/path.5022
|View full text |Cite
|
Sign up to set email alerts
|

Genomic classifications of renal cell carcinoma: a critical step towards the future application of personalized kidney cancer care with pan‐omics precision

Abstract: Over the past 20 years, classifications of kidney cancer have undergone major revisions based on morphological refinements and molecular characterizations. The 2016 WHO classification of renal tumors recognizes more than ten different renal cell carcinoma (RCC) subtypes. Furthermore, the marked inter-and intra-tumor heterogeneity of RCC is now well appreciated. Nevertheless, contemporary multi-omics studies of RCC, encompassing genomics, transcriptomics, proteomics, and metabolomics, not only highlight apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 140 publications
0
92
0
Order By: Relevance
“…The incidence and mortality of RCC have been increasing over the past two decades. (Bray et al, 2018;Escudier et al, 2016;Hsieh, Le, Cao, Cheng, & Creighton, 2018;Srigley et al, 2013) Kidney renal clear cell carcinoma (KIRC) is the most common subtype of RCC (70%-75%) and represents one of the most malignant genitourinary cancers. Nearly a quarter of patients were diagnosed with distal metastasis and advanced regional disease.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence and mortality of RCC have been increasing over the past two decades. (Bray et al, 2018;Escudier et al, 2016;Hsieh, Le, Cao, Cheng, & Creighton, 2018;Srigley et al, 2013) Kidney renal clear cell carcinoma (KIRC) is the most common subtype of RCC (70%-75%) and represents one of the most malignant genitourinary cancers. Nearly a quarter of patients were diagnosed with distal metastasis and advanced regional disease.…”
Section: Introductionmentioning
confidence: 99%
“…For many cancers, these efforts have led to new, integrated classifications in which genomic and histological features often align in a striking and highly informative fashion. This is exemplified in the present Annual Review Issue (ARI) by updates on the classification of renal cell carcinoma (Hsieh et al ) and endometrial carcinoma (McAlpine et al ). Conversely, in addition to uncovering novel and highly relevant subtypes of many cancers, these studies have also revealed robust and biologically plausible commonalities between cancers arising in different organs, as shown by the comparison of clear cell carcinomas of the ovary and kidney by Ji et al .…”
mentioning
confidence: 97%
“…The mutational phenotype of m-ccRCC patients suggests vascular endothelial growth factor (VEGF) and mechanistic target of rapamycin (mTOR) pathway as potential targets for successful treatment [6]. However, the use of targeted therapies, which include tyrosine kinase inhibitors (TKi) and mTOR inhibitors (mTORi), has extended the survival of patients with m-ccRCC only moderately, with an average of 14 to 24 months [7]. More recently, immunotherapeutics, including immune checkpoint inhibitors such as nivolumab (Nivo) and others have been approved by the FDA for m-ccRCC.…”
Section: Introductionmentioning
confidence: 99%